The impact of the MathMagic learning method on students’ mathematics cognitive learning outcomes - Desy Nursinta Al Kharomah; Muhammad Abduh (Jurnal Elemen, 2023)
Low cognitive learning outcomes of students can hinder student learning processes. This obstacle occurs because the learning method has yet to facilitate student learning trajectories resulting in low cognitive mathematics learning outcomes for students. The purpose of this research was to determine the impact of the MathMagic learning method on the mathematics cognitive learning outcomes of the students. The method used in this research was a quasi-experimental research design with a nonequivalent control group design. Data collection was done by test technique of students' cognitive learning outcomes. Data analysis techniques in this study used instrument tests in the form of validity and reliability tests, prerequisite tests in the form of normality tests and homogeneity tests, and hypothesis tests in the form of independent sample t-tests. The results show that the MathMagic learning method influenced students' cognitive learning outcomes in mathematics, especially in adding fractions with different denominators. This MathMagic learning method effectively improves understanding of the basic addition of fractions with unlike denominators.